Adaptation and validation of a measure of students? adaptive and maladaptive ways of coping with academic problems - Gon?alves, Teresa (2022)
Little research has, to date, explored students? coping in the academic domain. Yet, children and adolescents frequently refer daily academic difficulties as a common source of stress. The ways children respond to academic demands have the potential to make a difference in their learning and achievement. Therefore, the availability of a measure of academic coping is of critical importance to expand educational research and practice in this area. The current study adapted and validated the Portuguese language version of the Multidimensional Measure of Coping (MMC). Cognitive interviewing, confirmatory factor analysis, and measurement invariance testing using calibration and validation samples provided sound support for the validity of the MMC to measure academic coping among Portuguese elementary and middle school students. Furthermore, the external and discriminant validity of the scale was established based on the relations found between adaptive and maladaptive coping and their differential functionality for academic performance.